2021
DOI: 10.1186/s12890-021-01671-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in genetics and microenvironment of lung adenocarcinoma patients with or without TP53 mutation

Abstract: Background Differences in genetics and microenvironment of LUAD patients with or without TP53 mutation were analyzed to illustrate the role of TP53 mutation within the carcinogenesis of LUAD, which will provide new concepts for the treatment of LUAD. Methods In this study, we used genetics and clinical info from the TCGA database, including somatic mutations data, RNA-seq, miRNA-seq, and clinical data. More than one bioinformatics tools were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Zeng et al took the mutant group as a reference. There were significant differences in somatic mutation mRNA-seq miRNA-seq immune infiltration and immunomodulator in patients with mutant LUAD suggesting that TP53 mutation plays a key role in the occurrence and development of lung adenocarcinoma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al took the mutant group as a reference. There were significant differences in somatic mutation mRNA-seq miRNA-seq immune infiltration and immunomodulator in patients with mutant LUAD suggesting that TP53 mutation plays a key role in the occurrence and development of lung adenocarcinoma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that higher TMB and MSI in LUAD would probably induce a potent immunogenic neoantigen that improves the response to immune checkpoint inhibitor treatments [ 16 18 ]. A previous study has reported the effect of TP53 mutations on the immune checkpoints of patients with LUAD [ 19 ]. Additionally, Biton et al showed that TP53 mutations predict the response of patients with LUAD to anti-PD-1 through lymphocyte infiltration in the tumor immune microenvironment (TIME) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…NPY gene expression is upregulated in patients with lung adenocarcinoma and TP53 mutation [ 165 ]. Y1R has not been detected in non-small lung cancer cells [ 6 ].…”
Section: Involvement Of Neuropeptide Y Peptide Yy and Pancreatic Poly...mentioning
confidence: 99%